2020
DOI: 10.1186/s13690-020-00406-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adolescent deliveries and its complications in Cameroon: a systematic review and meta-analysis

Abstract: Background: Adolescent deliveries (10-19 years) carry a high risk of adverse outcomes due to the biological and physiological immaturity of these mothers. They pose a significant health burden in Cameroon, as it is reported that a high proportion of women attending delivery services are teenagers. We therefore sought to systematically assess the prevalence of adolescent deliveries in the country and its maternal and neonatal outcomes. Methods: This was a systematic review of literature and a meta-analysis. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…9 Adolescent deliveries carry a higher risk of adverse outcomes due to the immaturity of reproductive organs. 10 It was found that out of 4 teenage mothers, two had children either with nutritional deficiency or had childhood diseases. During the period of pregnancy, minimum 4 ANC visits are required to identify high risk pregnancy and also the early identification of major congenital anomalies.…”
Section: Resultsmentioning
confidence: 99%
“…9 Adolescent deliveries carry a higher risk of adverse outcomes due to the immaturity of reproductive organs. 10 It was found that out of 4 teenage mothers, two had children either with nutritional deficiency or had childhood diseases. During the period of pregnancy, minimum 4 ANC visits are required to identify high risk pregnancy and also the early identification of major congenital anomalies.…”
Section: Resultsmentioning
confidence: 99%
“…Campbell et al reported similar results in several SSA countries while Kumar et al found no relationship between maternal age and LOS in India [ 20 , 30 ]. On the contrary, Pereira et al and McMahon et al reported that adolescence was significantly associated with longer LOS following CS in Brazil and Tanzania, respectively [ 31 , 32 ]. Our findings were unexpected because the higher prevalence of childbirth complications among adolescents should necessitate longer LOS than in adults [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Self-discharge might be one of the drivers of the much higher odds of early discharge in the remote and rural Northern zone, where women might live far from health facilities and rely on infrequent transport. In these poorest zones of the country, the infrastructure (space, beds, privacy, water and sanitation) in health facilities might be suboptimal and could have motivated early self-discharge by women, as it was documented in rural Tanzania [ 32 ]. Health authorities should focus on those geographic zones when implementing the current national guidelines on LOS and PNC.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be speculated that the risk factors associated with adolescent pregnancy might trigger these adverse outcomes as well. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%